Language Learning Strategies And Readability Of Form Four KBD Arabic Textbooks - Ismail, Mohd Fadzli; Nik Yusoff, Nik Mohd Rahimi (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2021)
There have been efforts to empower the Arabic language as a subject with the potential to strengthen the Early Integrated Curriculum (KBD) in Malaysia. The importance of mastering this subject is also emphasized in the Malaysian Education Development Plan (2013-2025). Thus, the need to examine language learning strategies with students’ text readability is relevant. However, studies related to the readability of Arabic texts have been found to be limited and there are still weaknesses of students in using language learning strategies. Thus, this study aims to identify the relationship between language learning strategies and the readability of form four KBD Arabic textbooks among Government Aided Religious Schools (SABK) students. The Schema theory and the Interactive Reading Model by Rumelhart (1977) were used as the basis of this study. Meanwhile, quantitative design by survey was implemented on 694 students in five zones of SABK using the proportional strata random sampling technique. Data were analyzed descriptively and inferentially covering frequency, percentage, mean, standard deviation, Pearson correlation tests, and Kuder Richardson 20. The results of the study showed that the language learning strategies were at a moderate level. On the other hand, the level of readability of the Arabic textbooks of the students was disappointing. There was a weak significant positive relationship between language learning strategies and readability of form four KBD Arabic textbooks among SABK students. The implications of the study contributed to the applicability of the theories and models underpinned in the context of this study. The results of the study can also be used by teachers to help students improve their language learning strategies as well as to increase the readability achievement.